An improved procedure to assess the organic biodegradability and the biomethane potential of organic wastes for anaerobic digestion. Issue 7 (July 2019) - Teixeira Franco, Ruben; Coarita, Helen; Bayard, Rémy; Buffière, Pierre
In this study a fractionation procedure was developed and applied to evaluate the potential of some organic wastes (two cattle manures and two catch crops, fresh and after ensiling) for anaerobic digestion. This procedure was based on water extraction of the raw sample, which enabled the evaluation of the contributions of water-soluble and particulate phases to the investigated properties. Biomethane potential (BMP) and chemical oxygen demand (COD) were determined and used to assess the anaerobic biodegradability of raw materials. Analysis of structural carbohydrates, total Kjeldahl nitrogen, water-soluble carbohydrates, volatile fatty acids and pH were also included to explain the main phenomena involved in methane production from the tested biomass. Results show that the origin and the preparation mode had a significant impact on BMP distribution. Based on a COD balance, the biodegradability of the various feedstocks ranged from 45% to 75%. Biodegradability of fresh materials was negatively correlated with the sum of structural carbohydrates and lignin content. Among the feedstock used, the water-soluble phase represented 8–69% of the total COD and 7–46% to the total BMP. Solubilization of organic matter during ensiling was due to the production and accumulation of organic acids from particulate carbohydrates and organic nitrogen. This procedure detects kinetic and biodegradability differences among biomass and thus it can be useful for the design of anaerobic digestion plants. Furthermore, it can be applied to evaluate the efficiency of biomass pretreatments.